Cannabis for morning sickness: areas for intervention to decrease cannabis consumption during pregnancy - Karli Swenson (BMC, 2023)
Abstract Background Cannabis use during pregnancy is increasing, with 19-22% of patients testing positive at delivery in Colorado and California. Patients report using cannabis to alleviate their nausea and vomiting, anxiety, and pain. However, preclinical and clinical data highlight harmful effects to offspring physiology and behavior following fetal cannabis exposure. This narrative review identifies potential areas for intervention to decrease cannabis consumption during pregnancy. Methods A combination of keywords, including "cannabis", "cannabis", "weed", "pregnancy", "morning sickness", "child protective services", and "budtender" were searched in databases such as PubMed and Google Scholar, as well as in social media forums, governmental webpages, and other publicly available sources. Results The literature search identified several areas for intervention to reduce cannabis use during pregnancy, including physician and pharmacist training, engagement with pregnant patients, regulation of dispensary workers, and the role of child protective services. Discussion This comprehensive review identifies multiple areas for improvement to benefit pregnant patients. Recommendations are independent and can be implemented simultaneously by the identified groups. Limitations of this research includes the relatively limited availability of data focused specifically on cannabis consumption during pregnancy and the complexity of the sociopolitical field of substance use during pregnancy. Conclusions Cannabis consumption during pregnancy is increasing and causes harm to the developing fetus. To educate pregnant patients about these risks, we must address the gaps in education from multiple contact points.